STUDY OF THE STATE OF ENT-ORGANS IN CHILDREN WITH ANOMALIES AND DEFORMATIONS OF DENTOALVEOLAR APPARATUS AND SPEECH DISORDERS - P.S. Flis; N.V. Raschenko; A.O. Melnyk; V.V. Filonenko; O.I. Kotov (Ukrainian Medical Stomatological Academy, 2018)
The relevance of research. When examining patients with dentoalveolar anomalies, children with speech disorders can often be observed. For orthodontists, it is important to diagnose the etiologic component of these disorders, namely, whether they are the cause of diseases of the ENT-organs and whether they are directly related to orthodontic pathology. In order to study the impact of the pathology of the ENT-organs on the formation of speech disorders, clinical and additional examination methods were carried out. In case of respiratory tract narrowing due to the deviated septum, hypertrophic or allergic rhinitis, adenoid vegetations, hypertrophy of the tonsils, speech pathology may be observed. Specified pathologies are subject to treatment before the logopedic and orthodontic correction. According to our clinical study in children of the main group and of the comparison group, the apparent pathology of the nose and oropharynx was not detected. Subjective and objective methods of hearing examination also did not reveal deviations from the norm. For a more detailed study of the condition of the upper respiratory tract, it is advisable to use computer tomography of the skull and magnetic resonance therapy of the head. The purpose of research is to eliminate the influence of otorhinolaryngologic pathologies on the formation of speech disorders. Materials and methods. We examined 124 patients. Patients were divided into two groups: control and comparison. The control group consisted of 82 patients with anomalies and deformations of dentognathic apparatus and speech disorders. The comparison group consisted of 42 patients without orthodontic pathology who applied to otolaryngologists for a diagnostic examination. The examination did not show the expressed pathology of ENT-organs in the presence of speech impairment and 5 children (aged from 6 to 12 years) with ENT pathology and speech impairment were not included in the main comparison groups. To make clinical and additional diagnosis such methods as rhinoscopy, pharyngoscopy, otoscopy were used. Results and discussion. During the rhinoscopy of all the examined patients of control and comparison groups, it was found: the nasal passages were free, the nasal shells were of the usual size, the nasal membrane was in the medial position, pathological contents in the nasal cavity were not detected. During pharyngoscopy, attention was mainly paid to the size of palatine tonsils. Thus, 62 children (50%) had the 1st and 2nd stage of development, 42 (33.87%) - 2nd stage and 20 (16.13%) - II-III degree. Adenoids (nasopharyngeal tonsil) of the 1st and 2nd degree were established in 86 children (69.35%), 28 children (22.58%) - second degree and 10 (8.06%) - II-III degree, but in all children of the main and comparison groups, nasal breathing function was not noted. In 124 subjects (100%), there was no adenoid type of facial skeleton. Conclusion. With the narrowing of the respiratory tract due to a curvature of the nasal septum, hypertrophic or allergic rhinitis, adenoid vegetation, hypertrophy of the palatine tonsils, speech impairments can be observed. The specified pathologies are subject to treatment before the logopedic and orthodontic correction. According to our clinical examination of children of the main group and the groups of comparison, evident pathology of the nose and oropharynx was not detected. Subjective and objective methods of hearing examination also did not reveal deviations from the norm. For a more detailed study of the condition of the upper respiratory tract, it is advisable to use computer tomography of the skull and magnetic resonance therapy of the head.